A review of research trends in the enhancement of biomass-to-hydrogen conversion. (September 2018) - Mudhoo, Ackmez; Torres-Mayanga, Paulo C.; Forster-Carneiro, Tânia; Sivagurunathan, Periyasamy; Kumar, Gopalakrishnan; Komilis, Dimitrios; Sánchez, Antoni
Highlights: Cell immobilization significantly enhances biohydrogen generation rates and yields. Novel strains with higher cellulase turnovers improve biohydrogen synthesis. Integrated photo and dark fermentation systems improve biohydrogen production. Microwave irradiation, sonication and ionic liquids are green biomass pretreatments. Biological detoxification methods lower inhibitor levels and promote yield recovery. Abstract: Different types of biomass are being examined for their optimum hydrogen production potentials and actual hydrogen yields in different experimental set-ups and through different chemical synthetic routes. In this review, the observations emanating from research findings on the assessment of hydrogen synthesis kinetics during fermentation and gasification of different types of biomass substrates have been concisely surveyed from selected publications. This review revisits the recent progress reported in biomass-based hydrogen synthesis in the associated disciplines of microbial cell immobilization, bioreactor design and analysis, ultrasound-assisted, microwave-assisted and ionic liquid-assisted biomass pretreatments, development of new microbial strains, integrated production schemes, applications of nanocatalysis, subcritical and supercritical water processing, use of algae-based substrates and lastly inhibitor detoxification. The main observations from this review are that cell immobilization assists in optimizing the biomass fermentation performance by enhancing bead size, providing for adequate cell loading and improving mass transfer; there are novel and more potent bacterial and fungal strains which improve the fermentation process and impact on hydrogen yields positively; application of microwave irradiation and sonication and the use of ionic liquids in biomass pretreatment bring about enhanced delignification, and that supercritical water biomass processing and dosing with metal-based nanoparticles also assist in enhancing the kinetics of hydrogen synthesis. The research areas discussed in this work and their respective impacts on hydrogen synthesis from biomass are arguably standalone. Thence, further work is still required to explore the possibilities and techno-economic implications of combining these areas for developing robust and integrated biomass-to-hydrogen synthetic schemes.